The Effect of Social Media on the Language Use of Teenagers in Makassar - Marwah Juwita Yusuf; Syamsinar Syamsinar; Indrayani Simpuruh (Hasanuddin University, 2025)
The rapid rise of social media has significantly influenced how teenagers in urban areas like Makassar communicate. This study investigates the impact of social media platforms—such as Instagram, TikTok, and WhatsApp—on teenage language use, focusing on vocabulary, grammar, and communication styles. Employing a mixed-methods approach that includes surveys of 150 teenagers, interviews, and content analysis, the findings reveal that 85% of respondents frequently use internet slang and abbreviations, while 70% incorporate English loanwords in everyday speech. Common expressions like “DM,” “OOTD,” and “LOL” are now part of their daily lexicon, reflecting a shift toward a more globalized and informal linguistic environment. Qualitative analysis shows a trend toward simplified grammar in casual contexts and a growing reliance on emojis and memes for emotional expression. While these developments promote creativity, adaptability, and digital fluency, they also present challenges to formal language proficiency, especially in academic writing. This study concludes that social media acts as a double-edged sword—encouraging innovative language use while potentially weakening formal communication skills. It recommends integrating digital literacy and language awareness into school curricula to help students navigate and balance the demands of both informal and formal language contexts.